The beautiful country : tourism and the state of destination, Italy - Hom, Stephanie Malia, 1975- (Toronto Italian studies., 2015)
Using an interdisciplinary methodology that includes archival research, ethnographic fieldwork, literary criticism, and spatial analysis, The Beautiful Country reveals destination Italy's paramount role in the creation of modern mass tourism.